2021
DOI: 10.1113/jp281286
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycaemia enhances both vascular endothelial function and cardiac and skeletal muscle microvascular function in healthy humans

Abstract: Multiple clinical studies report that acute hyperglycaemia (induced by mixed meal or oral glucose) decreases arterial vascular function in healthy humans. Feeding, however, impacts autonomic output, blood pressure, and insulin and incretin secretion, which may themselves alter vascular function.r No prior studies have examined the effect of acute hyperglycaemia on both macro-and microvascular function while controlling plasma insulin concentrations.r Macrovascular and microvascular functional responses to eugl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 73 publications
(159 reference statements)
0
29
3
Order By: Relevance
“…This investigation was designed to explicitly compare intravenous and oral glucose administration routes while matching for glycaemia using variable‐rate glucose infusion. However, as a result of intravenous glucose administration, loss of the ‘incretin effect’ on pancreatic insulin output resulted in significantly suppressed insulinaemia for matched glycaemia, similarly occurring in Horton et al .’s (2021) investigation. As noted by the authors, insulin is a well‐studied vasodilator throughout the arterial system, and thus co‐infusion and matching of insulin and glucose would have produced a more physiologically relevant environment, further isolating the role of gut‐derived factors.…”
Section: Introductionmentioning
confidence: 69%
“…This investigation was designed to explicitly compare intravenous and oral glucose administration routes while matching for glycaemia using variable‐rate glucose infusion. However, as a result of intravenous glucose administration, loss of the ‘incretin effect’ on pancreatic insulin output resulted in significantly suppressed insulinaemia for matched glycaemia, similarly occurring in Horton et al .’s (2021) investigation. As noted by the authors, insulin is a well‐studied vasodilator throughout the arterial system, and thus co‐infusion and matching of insulin and glucose would have produced a more physiologically relevant environment, further isolating the role of gut‐derived factors.…”
Section: Introductionmentioning
confidence: 69%
“…Russell et al ( 39 ) reported that an oral glucose load decreased microvascular perfusion in healthy adults, though we did not see this in the healthy adolescents studied here. Interestingly, we recently found that in healthy adults, hyperglycemia (provoked by simultaneous intravenous glucose and octreotide infusion) acutely augments muscle microvascular perfusion ( 40 ). In contrast, both chronic insulin resistance [as seen with obesity ( 22 ), or metabolic syndrome ( 23 )] and acute insulin resistance induced by raising plasma free fatty acid concentrations ( 41 ) provoke muscle microvascular vasoconstriction similar to that seen here in persons with DM1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in healthy sportsmen with high exercise capacity, acute increases in blood viscosity were associated with increased NO production and improved vasodilatation, leading to enhanced vascular function (Connes et al 2012). Horton et al (2022) note that previous studies observing endothelial dysfunction with AH were condicted in populations that were diseased, obese and ageing. The aforementioned populations have been shown to engage in less exercise training and have increased sedentary behaviour (Zhou et al 2018), which may further explain the differences in vascular function observed during AH.…”
Section: Interpretations and Conclusionmentioning
confidence: 99%
“…Horton et al . (2022) eloquently demonstrated that AH enhances endothelial function, as well as cardiac and skeletal microvascular function, in healthy, young adults. These findings are in contrast to previous studies finding that AH induces vascular dysfunction, although Horton et al .…”
Section: Interpretations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation